Discogenic Back Pain: Literature Review of Definition, Diagnosis, and Treatment. (4th March 2019) - Fujii, Kengo; Yamazaki, Masashi; Kang, James D; Risbud, Makarand V; Cho, Samuel K; Qureshi, Sheeraz A; Hecht, Andrew C; Iatridis, James C
Abstract: Discogenic back pain is multifactorial; hence, physicians often struggle to identify the underlying source of the pain. As a result, discogenic back pain is often hard to treat—even more so when clinical treatment strategies are of questionable efficacy. Based on a broad literature review, our aim was to define discogenic back pain into a series of more specific and interacting pathologies, and to highlight the need to develop novel approaches and treatment strategies for this challenging and unmet clinical need. Discogenic pain involves degenerative changes of the intervertebral disc, including structural defects that result in biomechanical instability and inflammation. These degenerative changes in intervertebral discs closely intersect with the peripheral and central nervous systems to cause nerve sensitization and ingrowth; eventually central sensitization results in a chronic pain condition. Existing imaging modalities are nonspecific to pain symptoms, whereas discography methods that are more specific have known comorbidities based on intervertebral disc puncture and injection. As a result, alternative noninvasive and specific diagnostic methods are needed to better diagnose and identify specific conditions and sources of pain that can be more directly treated. Currently, there are many treatments/interventions for discogenic back pain. Nevertheless, many surgical approaches for discogenic pain have limited efficacy, thus accentuating the need for the development of novel treatments. Regenerative therapies, such as biologics, cell‐based therapy, intervertebral disc repair, and gene‐based therapy, offer the most promise and have many advantages over current therapies. © 2019 The Authors. JBMR Plus Published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research